The extraction and detection of zingiberene in zingiberaceae family by using headspace solid phase microextraction (Hs-Spme) with gas chromatography- mass spectrometry (Gc-Ms) / Nurzaimah Zaini @ Othman - Zaini @ Othman, Nurzaimah (2015)
Extraction conditions for the extraction and detection of zingiberene in zingiberaceae family by using headspace solid phase microextraction (HS-SPME) with gas chromatography - mass spectrometry (GC-MS) were optimized. SPME fiber coated with polydimethylsiloxane (PDMS) was used in this study. The effect of SPME extraction parameter such as extraction temperature, extraction time and desorption time on the peak area of zingiberene compound were studied. Optimum conditions for SPME technique in extracting zingiberene compound were 70 °C for extraction temperature, 10 minutes for the extraction time and 80 seconds for the desorption time. Using the optimized SPME condition, the compositions of zingiberene in ginger, turmeric and galangal were studied. Among them, ginger has the highest relative amount of zingiberene based on the peak area. Using the optimization condition also, the detection of zingiberene in three commercial ginger-containing products was conducted. Zingiberene can be detected in ginger tea brand A, but not in lotion brand A and brand B.